Legal Protection of Online-Based Transportation Workers in the Era of Digitalization - Indayatun, Ratna (Journal of Law, Politic and Humanities, 2025)
The objective of this research is to analyze the employment relationship between online transportation workers and their employers, examine why online transportation workers do not receive benefits from the Social Security Administration for Employment (BPJS Ketenagakerjaan) program, and assess the government's role in providing legal protection for online transportation workers. The research employs normative and sociological legal methods, utilizing secondary legal materials such as books, questionnaires, and interviews. Research Findings: The employment relationship between online transportation workers and their employers constitutes a permanent employment relationship (PKWTT) since it involves elements of work and wages. Online transportation workers receive legal protection from the Social Security Administration; however, this protection does not include the Old Age Security program. The government plays a role in providing legal protection to online transportation workers, as stipulated in Article 16, Paragraph (3) of Minister of Transportation Regulation No. PM 12 of 2019. However, in practice, online transportation workers have not fully received the social security benefits provided by the Social Security Administration for Employment (BPJS Ketenagakerjaan). Therefore, the government needs to provide guidance to employers and enforce laws and regulations related to the Old Age Security program in alignment with the digitalization era.